Effects of Functional Anterior Shifting On Skeletal and Airway Structures - Faruk İzzet Uçar; Gökmen Kurt; Abdullah Ekizer; Sabri İlhan Ramoğlu (Galenos Yayinevi, 2009)
To compare the maxillary and mandibular skeletal structures and airway dimensions between anterior functional shifting and Class I control patients. This study was composed of 48 patients. The first group was consisted of 24 patients (male: 11, female: 13). Mean ANB value was 0.31 ± 3.49 and mean age is 13.52 ± 2.95. The second group was a skeletal Class I group, and consisted of 24 patients (male: 7, female: 17) and served as the control group. Mean ANB was 2.47 ± 2.27 and mean age was 13.99 ± 1.79. Eighteen cephalometric measurements were used to evaluate skeletal differences, and 14 measurements were used for airway dimensions. Two groups were compared with independent t test. Position and size of the mandible were not affected with anterior functional shifting. S-Go distance was smaller in anterior functional shifting patients (p<0.05). Hard palate - soft palate angle was statistically lower (p< 0.01) and soft palate length (pns-spt) was higher (p<0.01) in anterior functional shifting group. Inferior airway measurement (sbti-phwl) represented higher values in functional anterior shifting group (p< 0.05). There were statistically significant differences in Pns-ppw1 (p< 0.05), spl/sps (p< 0.01) and spl/Ips (p< 0.01) measurements. Patients with anterior functional shifting showed wider airway than Class I control group. Postnatal maxillary development deficiency may be observed in functional anterior shifting cases.